KEBIJAKAN KOMUNIKASI DI KOTA MADIUN (Studi Kasus Pembentukan Perda No. 11 Tahun 2011 Tentang Lembaga Penyiaran Publik Lokal Radio Suara Madiun) - , Nurhana Marantika, Dr.Phil. Ana Nadhya Abrar, M.E.S ([Yogyakarta] : Universitas Gadjah Mada, 2013)
A communication policy decisions that will determine how the implementation of a state in the sense of organizing and harmonizing personal communication and human communication in the bond as citizens. Communication policy aims to ensure the public to be active and safe in the communication process, and ensuring the public to participate in controlling the development of the communication is happening to them. So also with Regulation No.11 of 2011 on Public Broadcasting Local Radio Voice Madiun, regulation about LPPL Suara Madiun Radio aims to provide legal protection for the LPPL Suara Madiun Radio. For all, the government of Madiun works day and night to produce a policy that will not complicate LPPL Suara Madiun Radio in carrying out his duties as a broadcast neutral, independent and thus able to control commercial and social cohesion, as well as the culture of the nation's preservation by continuing oriented to the interests of the whole society. Long process to go through Government Regulation No. Madiun in shape. 11 Year 2011 About the Public Broadcasting Local Suara Madiun Radio starting from planning, design, discussion, promulgation, dissemination and evaluation of regulations contained in the contents of this thesis. Anyone who is dominating the discussion of regulations to intrigue and values that influence the formation of regulation has been discussed in this thesis.